2019
DOI: 10.1111/hex.12919
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden and quality of life among early‐onset colorectal cancer survivors: A qualitative analysis

Abstract: BackgroundColorectal cancer (CRC) diagnosed at ages <50 years old (early‐onset CRC) has been increasing in the United States, resulting in a growing number of early‐onset CRC survivors who may face significant financial and quality of life (QOL) challenges.ObjectiveIdentify themes from a patient advocate discussion about the impact of CRC on financial burden and QOL among early‐onset CRC survivors.MethodsWe conducted a semi‐structured, stakeholder discussion among 14 early‐onset CRC survivors and one caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(100 citation statements)
references
References 30 publications
3
97
0
Order By: Relevance
“…We reduced the number of papers to 98 by reading the titles and abstracts. Subsequently, an additional 84 studies were excluded after reading the full texts, and 14 studies remained …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We reduced the number of papers to 98 by reading the titles and abstracts. Subsequently, an additional 84 studies were excluded after reading the full texts, and 14 studies remained …”
Section: Resultsmentioning
confidence: 99%
“…One study reported that the researchers' role may impact the interpretation of the findings . Three studies failed to provide sufficient details about the ethical approval process …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations